1978
DOI: 10.3189/s0022143000033463
|View full text |Cite
|
Sign up to set email alerts
|

The Orientation Polarization in Hexagonal Ice Parallel and Perpendicular to the c-axis

Abstract: ABSTRACT. The relative permittivity and loss of zon e-refi ned si ngle crys ta ls of hexagonal ice have been measured in the temperature range 200-271 K a nd freq u e ncy range 0.5 Hz-O.2 MHz, using brass, stainless steel, and gold-foil electrodes. The c-axis of the crystal was oriented parallel to the electric field in 14 samples a nd perpendicular to the field in 8 sampl es. The eq uilibrium relative permittivity of orientation polarization '0, parallel and perpendicula r to the c-axis, is 96.5 ± I and the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 28 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…The temperature dependence of ⑀ Ќ appears to go as 1 / T, indicating no ferroelectric ordering along that direction. On the other hand, one study found no appreciable difference between ⑀ ʈ and ⑀ Ќ , with the Curie-Weiss temperature for both being near 0 K. 29 Computational studies have examined the stabilities of the three structures ͑disordered, ferroelectric, and antiferroelectric proton ordered ice͒ using a variety of potential energy models. At the simplest level, interactions are described just as being between point charges on each water molecule.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature dependence of ⑀ Ќ appears to go as 1 / T, indicating no ferroelectric ordering along that direction. On the other hand, one study found no appreciable difference between ⑀ ʈ and ⑀ Ќ , with the Curie-Weiss temperature for both being near 0 K. 29 Computational studies have examined the stabilities of the three structures ͑disordered, ferroelectric, and antiferroelectric proton ordered ice͒ using a variety of potential energy models. At the simplest level, interactions are described just as being between point charges on each water molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed the dielectric anisotropy of ice is exploited in the characterisation of polar ice sheets by radio waves 8 as polycrystalline ice causes a distinct attenuation of radio waves in comparison to oriented ice. If all microscopic configurations of ice were energetically equivalent, as assumed in the Pauling model (see also Minagawa 9 ), the anisotropy ((ε − ε ⊥ )/ε ) would be vanishingly small (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The limiting permittivity at frequencies above the Debye relaxation has been determined in the course of normal dielectric measurements over the temperature range 200-230 °K by Johari and Jones [36], but for higher temperatures it was necessary to use special measurements in the range 1-100 MHz [37]. A typical value is s» = 3.16 ± 0.02 at 253 °K, falling to 3.14 at 200 °K.…”
Section: High Frequency Permittivity ? S» Of Pure Leementioning
confidence: 99%